EPID-06. DIAGNOSTIC INTERVAL TIME OF PEDIATRIC CNS TUMORS: A REPORT OF THE CANCER IN YOUNG PEOPLE IN CANADA (CYP-C) DATABASE. (4th December 2020) - AlNajjar, Mohammad; Goel, Divya; Larouche, Valerie; Erker, Craig; Cheng, Sylvia; Barber, Randy; Strother, Douglas; Sung, Lillian; Lafay-Cousin, Lucie
Abstract: INTRODUCTION: CNS tumors are the second most common neoplasm in children and have historically been associated with longer time to diagnosis. Data on the time-to-diagnosis for Canadian children with CNS tumors are limited and outdated. We aimed at evaluating the diagnostic interval time(DIT) for Canadian children, and identifying factors possibly associated with prolonged DIT. METHODS: Using the CYP-C database, we analyzed data from children <15 years, diagnosed with CNS tumors between 2001–2015. DIT was defined as time in weeks, elapsed from the first contact with a healthcare provider to confirming diagnosis. We described DIT according to patient's demographics, socioeconomic, geographic factors as well as tumor-related criteria. RESULTS: Patients from all Canadian provinces, except Ontario, had available timepoints to calculate DIT. The cohort included 842 patients. Mean DIT for all patients was 11.7 weeks(median 1.4). Gliomas had the longest mean DIT and embryonal tumors had the shortest(14.6 and 3.6 weeks p<0.01 ). ATRT and medulloblastoma had a mean DIT of 1.3 and 4.3 weeks respectively. DIT for HGG was shorter than for LGG (6.4 versus 16.1 weeks, p<0.01 ). Metastatic disease, infratentorial tumors, or age £36 months had significantly shorter DIT (5.6 vs 12.4 vs 18.4, 7.4 vs 13.1 and 8.6). Sex, annual income(QAIPPE), and distance from tertiary center did not influence DIT. CONCLUSION: The current diagnostic interval time for pediatric CNS tumors in Canada is 11.7 weeks(median 1.4weeks). These results only reflect the healthcare system's contribution toward diagnosis confirmation, but not the patient interval before seeking medical attention.